1996
DOI: 10.1103/physrevb.53.15106
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependence study of the spin glassCuMn (1%)

Abstract: We present a point-contact spectroscopy study on the spin glass CuMn ͑1%͒ using a mechanically controllable break junction. Here we can continuously vary the contact size d from 1 m down to the atomic regime and thereby investigate size effects in spin-spin ͑spin glass͒ and spin-conduction electron ͑Kondo͒ interactions. Differential resistance dV/dI as a function of bias voltage V has been determined for the above alloy at various d and in different applied magnetic fields up to 10 T. A characteristic spin gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…In this Letter, we report on measurements of the low temperature differential resistance R͑I͒ dV ͞dI of AuFe wires as a function of dc current bias I. As reported previously by other groups in measurements on CuCr wires [9] and point contact break-junction devices [10], we find that the shape of R͑I͒ reflects the behavior of the temperature dependent resistance R͑T ͒, in that it has a maximum at a particular current I m . In addition, however, we find that R͑I͒ is asymmetric in I, even in zero magnetic field.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…In this Letter, we report on measurements of the low temperature differential resistance R͑I͒ dV ͞dI of AuFe wires as a function of dc current bias I. As reported previously by other groups in measurements on CuCr wires [9] and point contact break-junction devices [10], we find that the shape of R͑I͒ reflects the behavior of the temperature dependent resistance R͑T ͒, in that it has a maximum at a particular current I m . In addition, however, we find that R͑I͒ is asymmetric in I, even in zero magnetic field.…”
supporting
confidence: 71%
“…For example, measurements by some groups [5,6] of the Kondo effect in thin films, wires, and small point contacts defined by break junctions show a definite size dependence, but on vastly different length scales, while mea-surements by other groups [7] on AuFe wires found no size dependence on the Kondo effect. The situation is similar for samples in the spin-glass regime [8][9][10][11]. Thus the issue of the existence of fundamental length scales in both the spin-glass and the Kondo regimes remains open.…”
mentioning
confidence: 99%
“…That effect may, however, show up in point contact experiments where the contact size is smaller by even more than one order of magnitude. Such experiments were performed by Yanson and his collaborators [16][17][18] with Mn and Fe impurities in Cu contacts. Zaránd and Udvardi [19,20] showed that depending on the actual position of the impurity the density of states for an essential energy range around the Fermi surface can be enhanced or depressed by even 20%, thus ρ = ρ 0 + δρ, where |δρ/ρ 0 | < 0.2.…”
Section: A Density Of States Effectsmentioning
confidence: 99%
“…Depending on the value of (Jρ 0 ) −1 that enhancement can be over a factor of 100 for Mn and about 2 − 3 for Fe impurities. The enhancement is the larger the smaller the Kondo temperature T K [16][17][18]20]. In the experiments the enhancement is the larger the smaller the contact size, thus to have large enhancement most of the impurities must be nearby the surface.…”
Section: A Density Of States Effectsmentioning
confidence: 99%
“…CuMn was chosen among others because it is a well studied system whose properties had been investigated in a broad range of compositions [37,38], spanning from diluted [39,40] to concentrated regimes [41,42,43] with a particular focus on the SG ordering [44,45,46,47]. As in all the SG alloys, the randomness in the position of the magnetic impurities and in the sign of the neighboring couplings in CuMn generate frustration and random distribution of coupling strengths and directions below a freezing temperature, T f , and results in the well-known Ruderman-Kittel-Kasuja-Yosida (RKKY) interaction [37].…”
Section: Single Cumn and Py Filmsmentioning
confidence: 99%